What evidence is there on the effectiveness of different models of delivering urgent care? A rapid review - Janette Turner; Joanne Coster; Duncan Chambers; Anna Cantrell; Viet-Hai Phung; Emma Knowles; Daniel Bradbury; Elizabeth Goyder (National Institute for Health Research, 2015)
Background: In 2013 NHS England set out its strategy for the development of an emergency and urgent care system that is more responsive to patients' needs, improves outcomes and delivers clinically excellent and safe care. Knowledge about the current evidence base on models for provision of safe and effective urgent care, and the gaps in evidence that need to be addressed, can support this process. Objective: The purpose of the evidence synthesis is to assess the nature and quality of the existing evidence base on delivery of emergency and urgent care services and identify gaps that require further primary research or evidence synthesis. Data sources: MEDLINE, EMBASE, The Cochrane Library, the Cumulative Index to Nursing and Allied Health Literature (CINAHL) and the Web of Science. Methods: We have conducted a rapid, framework-based, evidence synthesis approach. Five separate reviews linked to themes in the NHS England review were conducted. One general and five theme-specific database searches were conducted for the years 1995-2014. Relevant systematic reviews and additional primary research papers were included and narrative assessment of evidence quality was conducted for each review. Results: The review was completed in 6 months. In total, 45 systematic reviews and 102 primary research studies have been included across all five reviews. The key findings for each review are as follows: (1) demand - there is little empirical evidence to explain increases in demand for urgent care; (2) telephone triage - overall, these services provide appropriate and safe decision-making with high patient satisfaction, but the required clinical skill mix and effectiveness in a system is unclear; (3) extended paramedic roles have been implemented in various health settings and appear to be successful at reducing the number of transports to hospital, making safe decisions about the need for transport and delivering acceptable, cost-effective care out of hospital; (4) emergency department (ED) - the evidence on co-location of general practitioner services with EDs indicates that there is potential to improve care. The attempt to summarise the evidence about wider ED operations proved to be too complex and further focused reviews are needed; and (5) there is no empirical evidence to support the design and development of urgent care networks. Limitations: Although there is a large body of evidence on relevant interventions, much of it is weak, with only very small numbers of randomised controlled trials identified. Evidence is dominated by single-site studies, many of which were uncontrolled. Conclusions: The evidence gaps of most relevance to the delivery of services are (1) a requirement for more detailed understanding and mapping of the characteristics of demand to inform service planning; (2) assessment of the current state of urgent care network development and evaluation of the effectiveness of different models; and (3) expanding the current evidence base on existing interventions that are viewed as central to delivery of the NHS England plan by assessing the implications of increasing interventions at scale and measuring costs and system impact. It would be prudent to develop a national picture of existing pilot projects or interventions in development to support decisions about research commissioning. Funding: The National Institute for Health Research Health Services and Delivery Research Programme.